Official propositions for literacy instruction of children in the state of Pernambuco – Brazil: from national policies (BNCC and PNA) to state initiatives (Olhar de Professor, 2022)
This article discusses official propositions for literacy instruction of children in the state of Pernambuco, Brazil. In the light of the qualitative approach and documentary research, the aim is to understand the similarities and differences between the Common Core State Standards (BRASIL, 2018), the National Literacy Instruction Policy (BRASIL, 2019), the Curriculum of Pernambuco (PERNAMBUCO, 2019a) and the Literate Child Program (PERNAMBUCO, 2018a, 2018b), with regard to the theoretical, epistemological and didactic concepts recommended for the teaching and learning of reading and writing. The analyses revealed that, among the official propositions implemented in Pernambuco, there are antagonistic perspectives about the way they understand the literacy instruction process. While the State Standards and the National Literacy Instruction Policy are based on traditional perspectives, the Curriculum of Pernambuco and the Literate Child Program are aligned with the concept of literacy instruction from a literacy perspective.
Keywords: Official policies. Literacy instruction. Pernambuco.